2006
DOI: 10.1111/j.1468-2982.2005.01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Headache Prevention Outcome and Body Mass Index

Abstract: A population-based longitudinal study suggests that obesity is a strong risk factor for the development of headaches on 15 or more days per month. Little is know about the influence of weight on the response to headache preventive treatment. Herein we prospectively assessed the influence of the baseline body mass index (BMI) on the response to headache preventive treatment. We included adults with episodic or chronic migraine (ICHD-2), or transformed migraine (Silberstein and Lipton criteria) that sought care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 25 publications
(35 reference statements)
3
28
0
2
Order By: Relevance
“…Obese patients were reported to have 47% more headache or migraine than non-obese patients among 14000 young women aged between 18-23 years (24). A study of 30215 subjects found migraine symptoms in 3791; there was no association between migraine prevalence and increased BMI but an association was found between increased body weight with increased headache incidence and pain severity (25). A recent study in similar age groups found a relationship between migraine and obesity (26,27).…”
Section: Migraine In the Presence Of Insulin Resistance And Obesitymentioning
confidence: 99%
“…Obese patients were reported to have 47% more headache or migraine than non-obese patients among 14000 young women aged between 18-23 years (24). A study of 30215 subjects found migraine symptoms in 3791; there was no association between migraine prevalence and increased BMI but an association was found between increased body weight with increased headache incidence and pain severity (25). A recent study in similar age groups found a relationship between migraine and obesity (26,27).…”
Section: Migraine In the Presence Of Insulin Resistance And Obesitymentioning
confidence: 99%
“…. 17 Ford ve ark. 7601 kadın ve erkekte yaptıkları çalışmada, BKİ <18.5 ve BKİ>30 olan hastalarda migren riskinin yüksek olduğu bulunmuştur.…”
Section: Beden Kütle İndeksi̇ (Bki̇) Ve Mi̇grenunclassified
“…In addition to greater incidence and prevalence of migraine in morbid obese patient, a large body of studies revealed that there is the higher incidence of migraine severity among morbid obese women (40,41). Sample in a large survey in united states, Ford et al showed that increase in BMI is correlated with the elevated in severe migraines headache prevalence as a non-linear status (35).…”
Section: The Association Between Morbid Obesity and Migraine Headachementioning
confidence: 99%